Charming Nation: N. S. Harsha - Harsha, N. S. (Bombay; Gallery Chemould, 2006)
Exhibition catalog. Dec 2006-Jan 2007. Text: Grant Watson.
English
Keywords: 21st century; N4390-5098 Visual Arts. Exhibitions; India